Correlation Between Paramedic Disaster Triage Accuracy in Screen-Based Simulations and Immersive Simulations. (2nd January 2019) - Cicero, Mark X.; Whitfill, Travis; Walsh, Barbara; Diaz, Maria Carmen G.; Arteaga, Grace M.; Scherzer, Daniel J.; Goldberg, Scott A.; Madhok, Manu; Bowen, Angela; Paesano, Geno; Redlener, Michael; Munjal, Kevin; et al.
Abstract: Background: Disaster triage is an infrequent, high-stakes skill set used by emergency medical services (EMS) personnel. Screen-based simulation (SBS) provides easy access to asynchronous disaster triage education. However, it is unclear if the performance during a SBS correlates with immersive simulation performance.Methods: This was a nested cohort study within a randomized controlled trial (RCT). The RCT compared triage accuracy of paramedics and emergency medical technicians (EMTs) who completed an immersive simulation of a school shooting, interacted with an SBS for 13 weeks, and then completed the immersive simulation again. The participants were divided into two groups: those exposed vs. those not exposed to 60 Seconds to Survival © (60S), a disaster triage SBS. The aim of the study was to measure the correlation between SBS triage accuracy and immersive simulation triage accuracy. Improvements in triage accuracy were compared among participants in the nested study before and after interacting with 60S, and with improvements in triage accuracy in a previous study in which immersive simulations were used as an educational intervention.Results: Thirty-nine participants completed the SBS; 26 (67%) completed at least three game plays and were included in the evaluation of outcomes of interest. The mean number of plays was 8.5 (SD =7.4). Subjects correctly triaged 12.4% more patients in the immersive simulation at study completion (73.1% before, 85.8% after, P = 0.004). There was no correlation between the amount of improvement in overall SBS triage accuracy, instances of overtriage (P = 0.101), instances of undertriage (P = 0.523), and improvement in the second immersive simulation. A comparison of the pooled data from a previous immersive simulation study with the nested cohort data showed similar improvement in triage accuracy (P = 0.079).Conclusions: SBS education was associated with a significant increase in triage accuracy in an immersive simulation, although triage accuracy demonstrated in the SBS did not correlate with the performance in the immersive simulation. This improvement in accuracy was similar to the improvement seen when immersive simulation was used as the educational intervention in a previous study.